1989
DOI: 10.1097/00000658-198901000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Amino Acid Profiles in Sepsis and Stress

Abstract: Sepsis has been associated with specific plasma amino acid patterns. Sixty-five patients were prospectively investigated as to whether these patterns are indeed sepsis specific, or specific for metabolic stress without concomitant sepsis, or associated with the presence of organ failure. Virtually all aminoacid levels were decreased by 10-30% (p less than 0.05), whereas cystine and phenylalanine were significantly elevated. These changes were more pronounced in severe sepsis. Organ failure was not associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
1
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 17 publications
7
59
1
1
Order By: Relevance
“…The marked depletion of the nonessential amino acids glutamate, serine, glutamine, glycine, arginine, and ornithine as well as the reduction in total plasma amino acids are similar to previous reports in patients with sepsis or severe trauma (12,13). In addition to the nonessential amino acids, the concentrations of isoleucine and lysine were also reduced in the septic patients.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The marked depletion of the nonessential amino acids glutamate, serine, glutamine, glycine, arginine, and ornithine as well as the reduction in total plasma amino acids are similar to previous reports in patients with sepsis or severe trauma (12,13). In addition to the nonessential amino acids, the concentrations of isoleucine and lysine were also reduced in the septic patients.…”
Section: Resultssupporting
confidence: 89%
“…The results, however, are consistent with previous studies in septic rats (3,16) and patients (15) in which evidence was found that sepsis results in increased myofibrillar protein breakdown in skeletal muscle. In addition to muscle amino acid concentrations, several changes in plasma amino acids noticed here were similar to changes reported previously in patients with sepsis or trauma (12,13), further supporting the interpretation that our septic patients were in a catabolic state.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In an attempt to establish homeostasis, amino acids are released from peripheral tissues and shifted to the liver for promotion of hepatic protein synthesis, gluconeogenesis, and urea synthesis (24,25). Plasma amino acid concentrations in patients with sepsis or disease are lower than in persons without sepsis (17,30,49), and attempts have been made to use the extent of this difference as a marker of the severity and prognosis of the disease process (16,58). The uptake of amino acids by the liver is elevated, despite the reduced plasma amino acid concentration; thus, hepatic extraction of serum amino acids is increased (25).…”
mentioning
confidence: 99%
“…These cells seem to have a high dependence on ß-amino acid transport and calcium flux (66). Furthermore, other types of stress or injury such as surgical injury (61), cancer (33) and sepsis (63,86) have been correlated with decreased levels of plasma taurine.…”
Section: Structured Lipidsmentioning
confidence: 99%